Research on suicidal ideation in Colombia, 2010-2016 - Salamanca Camargo, Yenny; Siabato Macias, Elsa Fernanda (Pensando Psicología, 2017)
Introduction: Suicidal ideation has been considered as the first stage of the suicide spectrum and, therefore, the main predictor of future suicide attempts and even suicide, with an increased risk of suicide in the first year of suicidal ideation. Data reported, both globally and nationally, reflect a trend towards increased prevalence of suicidal behavior, thus becoming a public health problem. Objective: To know the findings related to suicidal ideation in the Colombian from the analysis of articles published between 2010 and 2016, retrieved from Redalyc, ScienceDirect, Medline, Mediclatina and Scopus information systems. Method: The search was carried out based on the abstracts found, linking psychology, medicine and social sciences. Results: A total of 22 articles were found in which suicidal ideation was studied independently or in relation to other variables, predominantly descriptive or correlational quantitative studies addressed mainly from clinical psychology, whose population group was adolescents and young adults. Conclusion: A strong academic and research interest in the clinical diagnosis of the cognitive component of suicide was identified, with a deficit in research related to the prevention or intervention of this risk factor, in spite of being considered a public health problem.